Cancer Risk in Type 2 Diabetes Mellitus: Metabolic Links and Therapeutic Considerations. (2nd June 2011) - Sun, Grace; Kashyap, Sangeeta R.
Abstract : Type 2 diabetes mellitus (DM2) is increasing in incidence, creating worldwide public health concerns and impacting morbidity and mortality rates. An increasing number of studies have demonstrated shared associations between DM2 and malignancy, including key clinical, biochemical, and metabolic commonalities. This paper will attempt to explore the relationship between the various types of cancer and diabetes, the common metabolic pathways underlying cancer development, and the potential impact of various antidiabetes therapies on cancer risk.